Polarization-switching dynamics in bulk ferroelectrics with isometric and oriented anisometric pores. (29th December 2016) - Khachaturyan, R; Zhukov, S; Schultheiß, J; Galassi, C; Reimuth, C; Koruza, J; von Seggern, H; Genenko, Y A
Abstract: Highly porous ferroelectric ceramics possess remarkably less polarizability than dense ceramics; instead they display high tunability of various physical properties. Particularly, the shape and orientation of pores as well as the total porosity exhibit a great effect on the polarization-switching dynamics. In the present work, finite-element simulations of the electric-field distributions and related statistical distributions of local switching times are analysed and compared with the switching characteristics of porous lead zirconate titanate ceramics, extracted from the experiment by means of the inhomogeneous field mechanism model of polarization switching. Surprisingly, the simulated statistical field-distributions turn out to be virtually independent of the pore-size distribution; however, they are sensitive to the anisometric shape and orientation of the pores. Additionally, they exhibit notable broadening with increasing porosity; an effect confirmed by experimental observations.